2022
DOI: 10.1021/acsami.1c22809
|View full text |Cite
|
Sign up to set email alerts
|

Simple Design Concept for Dual-Channel Detection of Ochratoxin A Based on Bifunctional Metal–Organic Framework

Abstract: A simple fluorescence and electrochemical dualchannel biosensor based on bifunctional Zr(IV)-based metal− organic framework (Zr-MOF) was proposed to detect Ochratoxin A (OTA). The bifunctional Zr-MOF, with photoluminescence properties and enormous electroactive ligands, was exploited to load OTA-specific aptamers for designing signal probes, greatly simplifying the probe-fabrication process and improving sensing reliability. Upon specific recognition of aptamer toward OTA, the anchored probe was released from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Ochratoxin A (OTA) is primarily generated through the consumption of improperly stored food products and uptake of OTA may cause organ damage. Recently, Li et al developed a Zr-MOFs-based fluorescent and electrochemical dual-channel biosensor for OTA detection [ 169 ]. As displayed in Figure 11 B, in the presence of OTA, its aptamer was released from the surface of Zr-MOFs due to the specific interaction between them.…”
Section: Biosensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ochratoxin A (OTA) is primarily generated through the consumption of improperly stored food products and uptake of OTA may cause organ damage. Recently, Li et al developed a Zr-MOFs-based fluorescent and electrochemical dual-channel biosensor for OTA detection [ 169 ]. As displayed in Figure 11 B, in the presence of OTA, its aptamer was released from the surface of Zr-MOFs due to the specific interaction between them.…”
Section: Biosensorsmentioning
confidence: 99%
“…( B ) Schematic illustration of the dual-channel Zr-MOFs-based detection strategy of OTA. Reproduced with permission [ 169 ]. Copyright 2022, American Chemical Society.…”
Section: Biosensorsmentioning
confidence: 99%
“…Additionally, Lin et al (2022) [ 67 ] demonstrated a Zr-MOF highly porous gold electrochemical and fluorescence dual-channel biosensor with a 1.0 × 10 −7 –0.14 × 10 −3 mg/L linear range and 2.4 × 10 −8 mg/L detection limit sensing ochratoxin A (OTA) in corn samples. Additionally, this sensor showed fluorescence intensity positively connected with that of OTA throughout a concentration range of 1.0 × 10 −7 to 0.16 × 10 −3 mg/L, with a detection limit of 5.1 × 10 −8 mg/L.…”
Section: Electrochemical Platforms For Sensing Different Mycotoxins I...mentioning
confidence: 99%
“… Graphical description of the dual-channel detecting of ochratoxin A (OTA). Adapted with permission from the article [ 67 ]. 2022, American Chemical Society.…”
Section: Figurementioning
confidence: 99%
“…5–7 For instance, continuous intake of animal-derived food products contaminated by TC residues can lead to decreased immunity, liver toxicity, allergic reactions, gastrointestinal disorders, genetic disorders and different types of cancer. 8–11 Many countries have developed relevant regulations on the maximum residue limit (MRL) of TC in foodstuffs, for example, the US Food and Drug Administration and the European Union stipulated that the MRL of TC in milk is 676 nmol L −1 and 225 nmol L −1 , 12 respectively, while China's relevant regulation is 100 g kg −1 (corresponding to 225 nmol L −1 ). Therefore, it is of utmost significance to develop a rapid and low-cost method for on-site monitoring of TCs for the well-being of human and environmental safety.…”
Section: Introductionmentioning
confidence: 99%